PENAMPILAN KARAKTER BEBERAPA GENOTIPE JAGUNG HIBRIDA PADA KONDISI KEKERINGAN - Marzuki, Maintang Intang; Efendi, Roy; Azrai, Muhammad (Informatika Pertanian, 2018)
Selection to identify corn genotypes that are able to use water effectively becomes a target in plant breeding activities to improve drought tolerance.  Research to determine the performance appearance of agronomic characters, morphology, and physiology of several hybrid genotypes has been carried out in the Experimental Field of Cereals Research Institute, Maros, South Sulawesi, June - October 2016 in drought stress conditions using 65 hybrid corn genotypes. The research was conducted with 65 corn hybrid genotypes arranged in a randomized completed block design with three replications.   Drought stress treatment was started before the flowering phase until the physiologically mature. The result indicated that agronomic, physiology and  yield characters that  are significant and positively correlated  with o grain yield  are plant height, ear  height, stalk diameter, leaf area, leaf chlorophyll, leaf moisture content, stomata area, wet ear weight, ear leght, number of ear harvest, number of grain/rows and weight of 1000 grain. Leave rolling score, leaf senescence and leaf temperature are physiological characters that haved  negative correlation with the grain yield, as well as agronomic characteristics of days to silking, days to anthesis and ASI value. Promising hybrid (CML 505/NEI 9008-9-5-B-B-B-B)// CY11, (CML 538/DMRYCML-2-7-B-B-B-B)//MAL03, (CML 538/DMRYCML-5-5-B-B-B-B)//MAL03, (CML 505/NEI 9008-9-4-B-B-B-B)//CY11, (CML 505/NEI 9008-18-2-B-B-B-B)//CY11, (CML 505/NEI 9008-9-1-B1-B-B-B)// CY11, (CML 538/DMRYCML-1-3-B-B-B-B)//CY11, (CML 505/NEI 9008-14-1-B-B-B-B)// B11209, (CML 505/NEI 9008-29-2-B-B-B-B)//CY11 dan (CML 505/NEI 9008-21-2-B-B-B-B)//MAL03 show better  agronomic performance, yield components andgrain yield potential than Bima 9, Bima 16, Pertiwi 3 and P31. Those promising hybrid  of drought tolerance could  be further developed.